DEVELOPING CRITICAL THINKING SKILLS THROUGH INTEGRATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN READING AND WRITING AT FERGANA STATE UNIVERSITY (Scientific journal of the Fergana State University, 2025)
This article explores the role of artificial intelligence (AI) technologies in developing critical thinking skills through reading and writing at Fergana State University. Employing a mixed-methods approach, the research combines quantitative surveys and qualitative insights to examine the impact of AI tools, such as writing assistants, grammar checkers, and summarization tools, on students' cognitive processes.